Native grass ground covers provide multiple ecosystem services in Californian vineyards. Issue 5 (25th March 2018) - Daane, Kent M.; Hogg, Brian N.; Wilson, Houston; Yokota, Glenn Y.
Abstract: Mechanisms responsible for the success or failure of agricultural diversification are often unknown. Most studies of arthropod pest management focus on enhancing natural enemy effectiveness. However, non‐crop plants can also change crop host quality by reducing or adding soil nutrients or water, and therefore improve or hamper pest suppression. Native perennial ground covers may provide food or habitat to natural enemies and, in terms of competition for soil nutrients or water, be more compatible with crop management than exotic annuals. We conducted a 3‐year vineyard study to examine the impacts of native perennial grasses on pests, natural enemies, crop plant condition and soil properties. We included three ground cover treatments: bare soil with a grower standard drip irrigation; native grasses with drip irrigation; and native grasses with drip irrigation as well as an additional flood irrigation to keep the grasses green and growing during the season. Numbers of leafhopper pests Erythroneura spp. decreased in both native grass treatments, where parasitism rates were higher. Vine petiole nitrate levels were lower in grass treatments, indicating competition for soil nitrogen, which is most often considered to be detrimental. Berry weight was higher in the irrigated treatment but did not differ between the bare soil and non‐irrigated grass treatment. Grape °Brix was similar in the bare soil and native grass treatments, suggesting native grasses did not compromise grape quality. In fact, leaf water stress was lower and soil moisture higher not only in the irrigated grass treatment but, at times, in the non‐irrigated grass treatment, compared with the bare soil treatment. Synthesis and applications . Our work shows that native grasses contribute to a reduction in vineyard leafhopper pests by reducing host quality through competition for soil nitrogen and providing food resources and/or habitat for natural enemies. Native grasses also improve soil water content and may be part of a water conservation program for perennial crops in dry climate regions. Abstract : Our work shows that native grasses contribute to a reduction in vineyard leafhopper pests by reducing host quality through competition for soil nitrogen and providing food resources and/or habitat for natural enemies. Native grasses also improve soil water content and may be part of a water conservation program for perennial crops in dry climate regions.